Second Look After Retromuscular Repair With the Combination of Absorbable and Permanent Meshes - Robin Valle de Lersundi, Alvaro; Munoz-Rodriguez, Joaquín; Lopez-Monclus, Javier; Blazquez Hernando, Luis Alberto; San Miguel, Carlos; Minaya, Ana; Perez-Flecha, Marina; Garcia-Urena, Miguel Angel (Frontiers in Surgery, 2021)
Objective: The aim of this study is to describe the macroscopic features and histologic details observed after retromuscular abdominal wall reconstruction with the combination of an absorbable mesh and a permanent mesh. Methods: We have considered all patients that underwent abdominal wall reconstruction (AWR) with the combination of two meshes that required to be reoperated for any reason. Data was extracted from a prospective multicenter study from 2012 to 2019. Macroscopic evaluation of parietal adhesions and histological analysis were carried out in this group of patients. Results: Among 466 patients with AWR, we identified 26 patients that underwent a reoperation after abdominal wall reconstruction using absorbable and permanent mesh. In 8 patients, the reoperation was related to abdominal wall issues: 4 patients were reoperated due to recurrence, 3 patients required an operation for chronic mesh infection and 1 patient for symptomatic bulging. A miscellanea of pathologies was the cause for reoperation in 18 patients. During the second surgical procedures made after a minimum of 3 months follow-up, a fibrous tissue between the permanent mesh covering and protecting the peritoneum was identified. This fibrous tissue facilitated blunt dissection between the permanent material and the peritoneum. Samples of this tissue were obtained for histological examination. No case of severe adhesions to the abdominal wall was seen. In 4 cases, the reoperation could be carried out laparoscopically with minimal adhesions from the previous procedure. Conclusions: The reoperations performed after the combination of absorbable and permanent meshes have shown that the absorbable mesh acts as a protective barrier and is replaced by a fibrous layer rich in collagen. In the cases requiring new hernia repair, the layer between peritoneum and permanent mesh could be dissected without special difficulty. Few intraperitoneal adhesions to the abdominal wall were observed, mainly filmy, easy to detach, facilitating reoperations.